Forensic mental health assessments in death penalty cases - DeMatteo, David, 1972- (New York ; Oxford : Oxford University Press, 2011)
This text provides an essential road map to forensic mental health assessments in death penalty cases for students and practitioners. The book integrates research with best practice recommendations, yielding a solid foundation of information related to capital punishment, death penalty litigation, and more.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Forensic psychiatry; Capital punishment; Mental status examination; Forensic psychology -- United States; Capital punishment -- United States; Mental status examination -- United States